2002
DOI: 10.1159/000064484
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Ca<sup>2+</sup> Balance Is Involved in the Stimulation of PTH Secretion

Abstract: The low calcium (Ca2+) dialysate have been developed to diminish the risk of hypercalcemia with the administration of active vitamin D and Ca2+ carbonate as phosphate binder. Today, increasing numbers of hemodialysis (HD) patients have been on the low Ca2+ dialysate (Ca2+ = 2.5 mEq/l). However, the clinical consequences of a negative calcium net-balance which may be induced by the use of low Ca dialysate are not well evaluated. In the present study, we explored the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Several patients did not tolerate long-term LCD treatment as their PTH level increased too rapidly; the PTH levels of the majority of the subjects increased only slightly and reached a stable level after 3–6 months, which is consistent with the results of related literature (21). The reason for this occurrence may be the oral administration of CaCO 3 during LCD treatment, which allows the PTH level to remain stable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several patients did not tolerate long-term LCD treatment as their PTH level increased too rapidly; the PTH levels of the majority of the subjects increased only slightly and reached a stable level after 3–6 months, which is consistent with the results of related literature (21). The reason for this occurrence may be the oral administration of CaCO 3 during LCD treatment, which allows the PTH level to remain stable.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the imbalance in Ca 2+ caused by the application of LCD may significantly stimulate the secretion of PTH (17). One study (18) confirmed that LCD alone significantly increases serum PTH, revealing that the increase of PTH is related to the decline of blood Ca 2+ and that PTH is restored to the level in the previous dialysis prior to the next dialysis. Ferreira et al (19) performed a one-year study of hemodialysis patients and identified that the iPTH levels significantly increased.…”
Section: Discussionmentioning
confidence: 96%
“…There was no complication of this approach and calcium levels were in desired ranges through the study. However, PTH levels may be acutely increased by using low‐dialysate calcium 26,27 . Finally, this was a small sample size, however, there is no previous study comparing these drugs with adjusted dose according to the pharmacokinetic study.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies have reported that a low calcium dialysate concentration increased serum i-PTH levels, 3,4,[13][14][15][16] while some studies of a low calcium dialysate concentration reported that high doses of calcium carbonate (mean dose, 6.2-10.5 g/day) could achieve adequate control of serum i-PTH and phosphorus levels. 2,5 We used a total calcium carbonate level of 4.1 g/day and the increment in total calcium carbonate was 0.5 g/day.…”
Section: Discussionmentioning
confidence: 99%